TATA KELOLA PRODUKSI KEDELE PADA PETANI NAGARI KOTO HILALANG DI KABUPATEN SOLOK - Hasdi Aimon (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2013)
This study is investigating and analyzing the soybean agriculture at Nagari Koto Hilalang in Solok. First of all, it will address the problems to the production of the soybean. Then the quality of the soy seed and the fertilizer which are used in the production of soy bean will be analyzed in order to optimize the harvest results. Finally, it will securitize the efficiency and the effectiveness of the soybean production. These issues will be discussed descriptively and associatively by using the primary data. There are 36 farmers which are involved in this study as the respondent. All the data were analyzed by using multiple regressions in order to optimize the production subject to the cost of production. The constant parameters are the farm land, and the labor. It finds out that the soy seed and fertilizer are giving significant influence to the soybean output. Also, the soybean production function is decreasing return to scale. The average production cost is Rp. 5.000.000 while the fixed cost is Rp.4.453.000 and variable cost is Rp. 547.000. The production soybean is 368,33 kg per hectare farm and the selling price is Rp. 12.000. As the consequence, the soybean agriculture is not benefit enough. Based on these results, it recommend to the local  government to conduct policy in the following sectors ; a) direct subsidize the price of seed and the fertilizer to the famers, b) ensuring the soybean market with national market price set by the government, c) education and training of downstream products from soybeans, so that the farmers become economically well establish